(untitled) (Far Western Review, 2025)
This study investigates the efficacy of value-based science instruction on the affective and cognitive domains of secondary-level students. Quantitative analysis was conducted to attain this purpose. The study was conducted in the Doiwala block of Dehradun district. On the basis of similarities on various parameters, control and experimental groups were made from students of ninth grade for the treatment, using purposive and random sampling and total 150 students were chosen as sample for experimentation and data gathering. Initially, pre-scores for both cognitive and affective domains were recorded. Lesson plans were developed for both conventional and value based teaching. The experimental group received value-based teaching, while the control group was taught using traditional methods for certain chapters. Following the teaching session, a post-test was administered to assess cognitive and affective outcomes. Using quantitative data on affective and cognitive dimensions, both groups were compared by ANCOVA, incorporating pre-test scores of cognitive and affective accomplishment, verbal intelligence, and socio-emotional school climate as covariates. Data analysis indicated that value-based scientific teaching significantly impacts students’ cognitive and affective abilities.